2020
DOI: 10.3390/nu12030739
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Comparative Efficacy of Metformin and Resveratrol in the Management of Diabetes-Associated Complications: A Systematic Review of Preclinical Studies

Abstract: Food-derived bioactive compounds such as resveratrol are increasingly explored for their protective effects against metabolic complications. Evidence supports the strong antioxidant properties and therapeutic effects of resveratrol in managing diabetes and its associated complications. However, evidence informing on the comparative or combination effects of this natural compound with an accomplished and well-characterized antidiabetic agent like metformin has not been revised. Thus, we conducted a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…At nutritionally relevant concentrations, resveratrol increases antioxidative enzyme gene expression and inhibits transcription of proinflammatory cytokines (Lejri et al, 2019;Rao et al, 2019). Previous studies have shown resveratrol promotes glucose metabolism as an adjunctive therapy for the management of diabetes-associated complications (Dludla et al, 2020). Additionally, resveratrol accelerates white adipocyte tissue browning (Li et al, 2020b) and fatty acid oxidation (Zhang et al, 2019d).…”
Section: Introductionmentioning
confidence: 99%
“…At nutritionally relevant concentrations, resveratrol increases antioxidative enzyme gene expression and inhibits transcription of proinflammatory cytokines (Lejri et al, 2019;Rao et al, 2019). Previous studies have shown resveratrol promotes glucose metabolism as an adjunctive therapy for the management of diabetes-associated complications (Dludla et al, 2020). Additionally, resveratrol accelerates white adipocyte tissue browning (Li et al, 2020b) and fatty acid oxidation (Zhang et al, 2019d).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplements and functional food ingredients are increasingly being explored for their diverse therapeutic capabilities [18,42,43]. As such, several dietary supplements have gained special interest due to their envisaged ameliorative effects against lifestyle diseases such as T2D and cardiovascular complications [17][18][19]23,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol is a non-flavonoid polyphenol that naturally occurs as phytoalexin and has been extensively studied in animal models and in diabetic humans [20,43,47]. This explains the general interest in understanding the therapeutic benefits of dietary supplements such as resveratrol in improving human health, especially their synergistic effects when used with established oral glucose-lowering drugs like metformin.…”
Section: Discussionmentioning
confidence: 99%
“…The antidiabetic synergistic effects of biguanides with certain natural substances have been determined. Several studies suggest a synergistic impact of resveratrol and metformin [ 234 ]. Furthermore, decreased blood glucose levels have been observed in STZ-induced diabetic rats receiving garlic extract in combination with metformin [ 235 ].…”
Section: Treatment Of Type 2 Diabetes Mellitusmentioning
confidence: 99%